2015
DOI: 10.1074/jbc.m115.645978
|View full text |Cite
|
Sign up to set email alerts
|

FBXO32 Targets c-Myc for Proteasomal Degradation and Inhibits c-Myc Activity

Abstract: Background: FBXO32 is an E3 ubiquitin ligase that plays important roles in tumorigenesis and muscle atrophy. Results: c-Myc was found to be a target of FBXO32 for proteasomal degradation. Conclusion: FBXO32 targets Lys-326 of c-Myc to form polyubiquitin chains, resulting in inhibition of cell proliferation. Significance: FBXO32 may mediate c-Myc proteasomal degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 47 publications
1
59
0
Order By: Relevance
“…The tumorigenesis ability of E3 ubiquitin ligase is also emerging with defined biological activities. Several E3 ubiquitin ligase, including NEDD4 5, 10, ITCH 11, WWP2 12, 13, and FBXO32 6 have been confirmed to be related with the tumorigenesis. In order to find the tongue cancer‐related E3 ligases, we screened the human E3 ubiquitin ligase library and found the candidate molecule, RNF126.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The tumorigenesis ability of E3 ubiquitin ligase is also emerging with defined biological activities. Several E3 ubiquitin ligase, including NEDD4 5, 10, ITCH 11, WWP2 12, 13, and FBXO32 6 have been confirmed to be related with the tumorigenesis. In order to find the tongue cancer‐related E3 ligases, we screened the human E3 ubiquitin ligase library and found the candidate molecule, RNF126.…”
Section: Discussionmentioning
confidence: 97%
“…The aberrant accumulation of oncoprotein which results from the abnormal proteolysis, contributes to the origination and progression of cancer. Previous studies have suggested that E3 ubiquitin ligase were involved in the occurrence of lung cancer, breast cancer, and oral cancer 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…Further research indicated that, in vivo, the size of tumor was significant reduced after intratumoral administration of the cholesterol-conjugated miR-197 mimics, which emphasized the role of miR-197 in tumor suppression (Li et al, 2006b). In addition, with overexpression miR-197, c-Myc, Bcl-2 and MMP-2, three of which are downstream targets of IL-6/STAT3 signaling pathway and tightly related to cancers (Martinou and Youle, 2011;Mei et al, 2015;Ma et al, 2015), decreased distinctly .…”
Section: Mir-197 In Tumor Suppressorsmentioning
confidence: 94%
“…31,32 In addition, a recent study identified the classic oncogene c-Myc as an ubiquitination substrate of FBXO32, supporting the speculation that FBXO32 acts as a tumor suppressor in cancer development. 33 Currently, the role of FBXO32 in tumorigenesis still remains unclear, and the underlying mechanism is poorly understood.…”
Section: Introductionmentioning
confidence: 99%